Pelatihan Pembelajaran Kimia Melalui Aplikasi Chemistry Access di SKH IT YARFIN - Bilqis, Ega Viranti Intana; Santoso, Clarinta Fadheela; Jasmin, Maulina; Salman, Rizky; Dewi, Lestari Kumala; Rahmawati, Yuli (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
Abstract This article discusses the development of an Android-based multimedia application as a chemistry learning media for visually impaired students on the topic of electrolyte and non-electrolyte solutions. This multimedia application is named Chemistry Access. Chemistry Access was developed to meet the needs of inclusive learning media for visually impaired students. The application development process includes needs analysis, design, creation, testing, and evaluation. The results showed that Chemistry Access could improve visually impaired students' understanding of electrolyte and non-electrolyte solutions materials. The students and teachers' responses to this application were also positive. Based on the evaluation results, it can be concluded that Chemistry Access is effectively used as an inclusive chemistry learning media that meets the special needs of visually impaired students. Abstrak Artikel ini membahas tentang pengembangan aplikasi multimedia berbasis android sebagai media pembelajaran kimia untuk siswa tunanetra pada materi larutan elektrolit dan non elektrolit. Aplikasi multimedia ini diberi nama Chemistry Access. Chemistry Access dilakukan untuk memenuhi kebutuhan media pembelajaran yang inklusif bagi siswa tunanetra. Proses pengembangan aplikasi meliputi tahap analisis kebutuhan, desain, pembuatan, uji coba, hingga evaluasi. Hasil penelitian menunjukkan bahwa Chemistry Access mampu meningkatkan pemahaman siswa tunanetra terhadap materi larutan elektrolit dan non elektrolit. Respon siswa dan guru terhadap aplikasi ini pun positif. Berdasarkan hasil evaluasi, dapat disimpulkan bahwa Chemistry Access efektif digunakan sebagai media pembelajaran kimia yang inklusif bagi kebutuhan khusus siswa tunanetra.